ANALISIS PERAN USAHA MIKRO, KECIL DAN MENENGAH TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA - jamiyatuz zulfiyyah (Sekolah Tinggi Pariwisata Mataram, 2021)
Micro, Small and Medium Enterprises (MSMEs) are innovations that can be used as a strong foundation for a country, especially Indonesia which is still at the level of a developing country, it is hoped that MSMEs can play an important role in the economy in Indonesia, looking at Indonesia's history of experiencing a monetary crisis in this Micro, Small and Medium Enterprises (MSMEs) were able to survive and tended to increase at that time, while many large-scale businesses suffered losses and even went bankrupt. This study uses a descriptive qualitative approach, describing the data objectively. The formulation of the problem used in this study is how many companies / businesses and the extent of the spread of MSMEs in absorbing labor in Indonesia, and how the role of MSMEs in reducing the unemployment rate in Indonesia. The results of this study reveal that MSMEs have a dominant role in absorbing labor in Indonesia, from year to year the number of MSMEs has always increased significantly, their numbers are always above the number of large-scale businesses. In line with the increase in MSMEs, employment has increased significantly. So that MSMEs play an important role in reducing the unemployment rate in Indonesia. Keywords: MSMEs & Labor